Forensic Accounting Practices and Management of Public Funds in Nigeria: An Empirical Study - Obiorah Maxwell ILOCHI (Journal of Accounting and Financial Management, 2026)
This study critically evaluates the relevance of forensic accounting practices on the management of public funds in Nigeria. Specifically, it intends to examine the impact of the deployment of Forensic investigative skills on detection and prevention of financial fraud in Nigeria. It also intends to evaluate the effect of forensic accounting practices on the recovery of misappropriated public funds in Nigeria. Survey research design was adopted and the primary source of data collection through a 5-point Likert rating scale structured questionnaire used. A total of 305 professional members of ICAN and ANAN were purposively sampled and data responses obtained were duly analysed using One Sample T-test analytical technique. Findings obtained showed that a strong and positive relationship exists between forensic accounting practices and detection/prevention of financial fraud which significantly facilitates management of public funds in Nigeria, though significant difference persists in this Professional opinion. The study also found a strong and positive significant relationship between forensic accounting practice in public service and the recovery of misappropriated public funds in Nigeria. Therefore, the study concludes that the application of forensic accounting practice in the Nigerian public sector will not only create sustainable blockades to corrupt activities but will secure Investors and creditors confidence and ensure optimum utilization of scarce financial and non-financial resources, thus further smoothening the path to the optimal management of public funds in Nigeria. The study therefore recommends inter alia that Forensic Accountants should be employed to closely comonitor the maximisation of voted funds towards ensuring that such funds are utilized for the intended purposes.